E-government as a connected ecosystem: Patterns, trends, and future paths in a bibliometric review - Ahmad Muhardin Hadmar; Anwar Sadat; Nur Inzana (Faculty of Social and Political Science, Universitas Airlangga, 2026)
Global digitalization is driving changes in e-government, forcing governments to adapt to society’s evolving needs. This study analyses e-government research conducted through bibliometric methods, with publications in the Scopus database from 2020–2025. The research methodology involves a literature analysis using VOSviewer software to illustrate the relationship between themes, authors, affiliations, and research patterns. The findings indicate that the number of e-government publications fluctuated, with the highest amplitude in 2022, and was dominated by social sciences at 55%. The main participants were Aswar K., Androniceanu A., and Georgescu I., as well as the University of Economic Studies Bucharest, Riau University, and UPN Veteran Jakarta. Digital transmission, technological literacy, public participation, transparency, and corruption were among the trending topics. Furthermore, Denmark ranked first based on the e-Government Development Index (EGDI), with an average of 0.97741. These results verify that the dynamics of e-government depend on policy aspects, digital infrastructure, and human resource capacity. The study also recommends that the government strengthen inclusive policies, improve digital literacy, and build infrastructure and a smart workforce for sustainable digital transformation.